Empowering settings and voices for social changes - Aber, Mark S.; Maton, Kenneth I.; Seidman, Edward (New York, 2011)
"Empowering Settings and Voices for Social Change combines a focus on understanding social settings as loci for empowering intervention with a focus on understanding and giving voice to citizens. The volume illuminates advances in theory and method relevant to changing a broad spectrum of social settings (including programs, organizations, institutions, communities and social policy) from a strengths-based perspective. Three cross-cutting concepts -- a strengths-based approach to research and social action, empowerment, and narrative research methods -- serve as integrating and foundational themes.